Aberrant DNA hypermethylation-silenced SOX21-AS1 gene expression and its clinical importance in oral cancer. Issue 1 (December 2016) - Yang, Cheng-Mei; Wang, Tsung-Han; Chen, Hung-Chih; Li, Sung-Chou; Lee, Ming-Chien; Liou, Huei-Han; Liu, Pei-Feng; Tseng, Yu-Kai; Shiue, Yow-Ling; Ger, Luo-Ping; Tsai, Kuo-Wang
Abstract Background Long noncoding RNAs (lncRNAs) are more than 200 nucleotides in length and lack transcriptional ability. The biological function of lncRNAs in oral squamous cell carcinoma (OSCC) remains unclear. The aim of this study was to identify the dysfunction of lncRNA in OSCC. Results We analyzed the transcriptome profiles of human OSCC tissues and paired adjacent normal tissues from two patients through a next-generation sequencing approach. A total of 14 lncRNAs were upregulated (fold change ≥3) and 13 were downregulated (fold change ≤−3) in OSCC tissues compared with the adjacent normal tissues. SOX21-AS1 was subjected to further analysis, revealing that the expression levels of SOX21-AS1 significantly decreased in OSCC compared with the adjacent normal tissue. The promoter activity of SOX21-AS1 was obviously suppressed by in vitro methylation. The DNA methylation status of the SOX21-AS1 promoter was analyzed using combined bisulfite restriction analysis, revealing that the aberrant promoter hypermethylation of SOX21-AS1 was observed frequently in OSCC tissues. The effects of SOX21-AS1 on cell proliferation and invasion were examined through transient transfection. Our data showed that SOX21-AS1 could significantly suppress oral cancer cell growth and invasion. Furthermore, the low expression level of SOX21-AS1 was significantly correlated with an advanced stage (P = 0.047), large tumor size (P = 0.033), and poor disease-specific survival in OSCC patients (P = 0.002). Conclusions SOX21-AS1 was identified as susceptible dysfunction correlated with promoter hypermethylation in OSCC. Low SOX21-AS1 expression may be an adverse prognostic biomarker for OSCC.